Targeted Intraoperative Radiotherapy (TARGIT-IORT) for Early-Stage Invasive Breast Cancer: A Single Institution Experience - Brown, Andrea; Buss, Elizabeth J.; Chin, Christine; Liu, Gaotong; Lee, Shing; Rao, Roshni; Taback, Brett; Wiechmann, Lisa; Horowitz, David; Choi, Julie C.; Katz, Leah M.; Connolly, Eileen P. (Frontiers in Oncology, 2022)
Purpose/Objective: We present our single-institution experience in the management of invasive breast cancer with intraoperative radiation therapy (IORT), focusing on patient suitability for IORT determined by the American Society for Radiation Oncology (ASTRO) Accelerated Partial Breast Irradiation (APBI) consensus guidelines. Materials/Methods: We identified 237 patients treated for biopsy-proven early-stage invasive breast cancer using low energy x-ray IORT at the time of lumpectomy between September 2013 and April 2020 who were prospectively enrolled in an institutional review board (IRB) approved database. We retrospectively reviewed preoperative and postoperative clinicopathologic factors to determine each patient’s ASTRO APBI suitability (suitable, cautionary or unsuitable) according to the 2017 consensus guidelines (CG). Change in suitability group was determined based on final pathology. Kaplan-Meier methods were used to estimate the survival probability and recurrence probability across time. Results: Based on preoperative clinicopathologic characteristics, 191 (80.6%) patients were suitable, 46 (19.4%) were cautionary and none were deemed unsuitable. Suitability classification changed in 95 (40%) patients based on final pathology from the time of surgery. Increasing preoperative lesion size or a BMI > 30 kg/m2 were significant predictors for suitability group change. Forty-one (17.3%) patients received additional adjuvant whole breast radiotherapy after IORT. At a median follow up of 38.2 months (range 0.4 – 74.5), five (2.1%) patients had ipsilateral breast tumor recurrences (IBTR), including 2 (0.8%) true local recurrences located <2cm from the initial lumpectomy bed with the same histology as the initial tumor. Ipsilateral breast tumor recurrence occurred in one patient in the suitable group, four patients in the cautionary group, and no patients in the unsuitable group. Conclusion: There is a low rate of IBTR after IORT when used in appropriately selected patients. Change in suitability classification pre to postoperatively is common, highlighting a need for further investigation to optimize preoperative patient risk stratification in this setting. Patients who become cautionary or unsuitable based on final pathology should be considered for additional adjuvant therapy.